2021
DOI: 10.3390/vaccines9080806
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 by SARS-CoV-2 Lineage B.1.1.7 in Vaccinated Solid-Organ Transplant Recipients: New Preventive Strategies Needed to Protect Immunocompromised Patients

Abstract: Background: Solid-organ transplant (SOT) recipients are at a high risk of severe COVID-19, and are priority for vaccination. Here, we describe three cases of severe COVID-19 caused by SARS-CoV-2 B.1.1.7 lineage in vaccinated SOT recipients. Methods: Three SOT patients were hospitalized in the Policlinico Hospital of Bari (southern Italy) and underwent nasopharyngeal swabs for molecular detection of SARS-CoV-2 genes and spike protein mutations by real-time PCR. One sample was subjected to whole-genome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The full text of 18 studies was further evaluated for eligibility. Of these, 12 articles were eligible to be included into this systematic review [17][18][19][20][21][24][25][26][27][28][29][30] (Figure 1). This encompassed a total of 563 HTX recipients with an average age of 60.8 years (range: 18-80), who received at least 1 dose of SARS-CoV-2 vaccine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full text of 18 studies was further evaluated for eligibility. Of these, 12 articles were eligible to be included into this systematic review [17][18][19][20][21][24][25][26][27][28][29][30] (Figure 1). This encompassed a total of 563 HTX recipients with an average age of 60.8 years (range: 18-80), who received at least 1 dose of SARS-CoV-2 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…This encompassed a total of 563 HTX recipients with an average age of 60.8 years (range: 18-80), who received at least 1 dose of SARS-CoV-2 vaccine. Out of the studies with a reported gender distribution (496 patients), [17][18][19][20][24][25][26][27][28]30 319 were male (64.3%) and 177 were female (35.7%). The patient population enrolled in these studies were from Israel, 24,[26][27][28] Europe (Italy, Spain, Germany, and Greece), 17,[19][20][21]29 Taiwan, 30 and the USA 18,25 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Case series of severe SARS-CoV-2 infections in fully vaccinated KTRs have been reported. 95,96 A recent large multicenter study showed that compared with 101 million fully vaccinated adults in the United States, fully vaccinated SOT recipients (n = 18.215) had an 82-fold higher risk of breakthrough infection and 485-fold higher risk of breakthrough infection with associated hospitalization and death. 97 These data emphasize the importance of the adaptative immune response in the defense against the virus.…”
Section: Immunosuppression and Anti-sars-cov-2 Vaccinesmentioning
confidence: 99%
“…[15][16][17][18][19][20] Indeed, initial studies reported that, despite being vaccinated, SOT patients still became infected with SARS-CoV-2 and required hospitalization, highlighting the necessity of novel strategies to protect this vulnerable population. [21][22][23] SARS-CoV-2-specific T cells have been detected in convalescent patients in multiple studies, indicating an important role for T cells in viral clearance and development of protective immunity. [24][25][26] Thus, SARS-CoV2-specific adoptive T cell therapy (ACT) has been suggested as an early treatment or preventive strategy for COVID-19 in immunocompromised or immunosuppressed individuals 27 as well as more generally for treatment of acute COVID-19.…”
Section: Introductionmentioning
confidence: 99%